In vitro modulation of human gut microbiota composition and metabolites by Bifidobacterium longum BB-46 and a citric pectin - Bianchi, Fernanda [UNESP]; Larsen, Nadja; Tieghi, Thatiana de Mello [UNESP]; Adorno, Maria Angela T.; Saad, Susana M.I.; Jespersen, Lene; Sivieri, Katia [UNESP] (Elsevier, 2019)
The gut microbiota composition and its metabolites have high impact on human health. Exploitation of prebiotics and probiotics for modulation of gut microbiota can lead to promising outcomes. This study aimed to evaluate the effects of the probiotic strain Bifidobacterium longum BB-46 alone and in combination with a citric pectin from lemon on the gut microbiota from healthy adults using the Simulator of Human Intestinal Microbial Ecosystem (SHIME ® ). Changes in microbiota composition and in metabolic activity were assessed by the 16S rRNA gene sequencing and by analyses of short-chain fatty acids (SCFAs) and ammonium ions (NH 4 + ). An increase in the relative abundances of Firmicutes (especially the members of Lachnospiraceae and Lactobacillaceae families) and Bacteroidetes was observed during treatment with B. longum BB-46 alone in all compartments of the colon. Treatment with B. longum BB-46 and pectin stimulated an increase in the proportions of genera Faecalibacterium, Eubacterium and Lactobacillus, as well as in the Ruminococcaceae family in the transverse and descending colons. Concurrently, the butyrate levels increased in these two compartments. Additionally, the combination of B. longum BB-46 and pectin reduced the abundance of proteolytic bacteria Bacteroides, Clostridium, Peptoniphilus, and Streptococcus, along with decreased NH 4 + production. No significant changes could be observed on NH 4 + production by treatment with B. longum BB-46, nor did it increase the amount of SCFAs. In this study, we observed that although each treatment was able to modulate the microbiota, the combination of B. longum BB-46 and pectin was more efficient in decreasing the intestinal NH 4 + levels and in increasing butyric acid-producing bacteria. These findings indicate that B. longum BB-46, especially when combined with the specific citric pectin, might have beneficial impact on human health.
Keywords: 16S rRNA gene sequencing; Bifidobacterium longum BB-46; Human gut microbiota; Metabolites; Pectin; SHIME ®